Pemanfaatan Daun Lamtoro Dan Ekstrak Tauge Dengan Penambahan Urine Sapi Untuk Pembuatan Pupuk Organik Cair - Listiyana, Rita; , Dra. Aminah Asngad, M.Si (2016)
Liquid organic fertilizer is a fertilizer in the form of a solution from the decomposition of organic materials derived from crop residues and animal dung haranya element content of more than one element. Leucaena leaf extract, extract of bean sprouts and cow urine can be combined to produce a liquid organic fertilizer. Nitrogen, phosphorus, potassium, calcium, iron and magnesium is a compound contained in leucaena leaf extract, extract of bean sprouts and cow urine. The purpose of this study to determine the content of nitrogen and phosphorus in liquid organic fertilizer from leucaena leaf extract and extract of bean sprouts with the addition of cow urine. This research method completely randomized design (RAL) with two factors, a factor of 1: leaf extract volume leucaena 82 ml: extract bean sprouts 168 ml (K1), the volume of leaf extract leucaena 125 ml: extract bean sprouts 125 ml (K2), the volume of leaf extract leucaena 168 ml: 82 ml extract of bean sprouts (K3) and a factor of 2: volume urine cows 75 ml (I1), 80 ml (I2), 85 ml (I3). Parameters observed that the content of N and P in the liquid organic fertilizer. The results showed that the highest nitrogen content contained in K3I1 treatment is 0.40% and the nitrogen content was lowest for the treatment K1I1 0.15 ml. While phosphorus content is highest at treatment K2I1 is 185.61 ppm and phosphorus content was lowest for the treatment K3I2 of 118.46 ppm.